Pemanfaatan Tanaman oleh Etnis Tionghoa dalam Ibadah di Beberapa Vihara di Kota Medan - Indah Kemalasari; Jamilah Nasution; Ferdinand Susilo (Universitas Medan Area, 2019)
Chinese is one of the ethnic that use some plants for their ceremony needs as well certain ritual and therapy for most illness. This research about utilization of plants for Chinese etnic of prayer ceremony. The purpose of this reseacrh was to asses some kinds of useful plants among Chinese ethnic for their praying ceremony in some Viharas in Medan with their specific function. This reseacrh used descriptive qualitative method through emic and ethnic approach. Based on the observations which were carried out in 5 Viharas in Medan 29 kinds of plants 18 families were used for prayer ceremony purposes. 50% of these plant were used for offerings without being processed as remaining 50% were processed as food/beverages which were used for offerings as well. Regarding to functional parts, 3% of these plants were used utilizing the plant’s stem, leaves (13%), flowers (19%), fruits (32%), seeds (13%), beets (10%), and some of them were used as whole plant which represented as 10% of whole species